Formation of the Value-based Attitude Towards Health Among Lyceum Students - Наталья А. Шмойлова; Дмитрий В. Каширский (Rossijskij psihologičeskij žurnal., 2021)
Introduction. This paper introduces the idea of three associated components of the value-based attitude towards health which is represented in individual consciousness at the level of meanings, senses, and sensory fabric. Specific psychological and pedagogical conditions aimed at the development of these components in students facilitate an increase in the level of importance of the value of health, an improvement in psychological well-being, and an increase in the level of self-actualization, which contributes to the fact that the value-based attitude towards health becomes an effective regulator of individual behavior and activities. Methods. The study used the KVS-3 for diagnosing the value system (D. V. Kashirsky), the Self-Actualization Test (SAT), the Scale of Psychological Well-being (K. Riff), and the questionnaire for diagnosing the Value of Health in the Psychological Structure of Consciousness (N. A. Shmoylova). Results and Discussion. In the ascertaining experiment, we observed no significant differences between the experimental and control groups of subjects. Meanwhile, the external (‘nominal’) level of meanings was predominant in the structure of the value of health. The degree of representation of the value of health in the form of subjective senses and sensory images was much less pronounced in students’ consciousness. The respondents of the experimental group took part in the forming experiment, when we implemented a program to form their general ideas of maintaining a healthy lifestyle, to saturate the value of health with personal senses, and to enrich the inner value-based world with the sensory, emotional, and need-related content related to health. We found that the harmonious presence of the value of health in students’ consciousness at the level of objective meanings, subjective senses, and the sensory fabric of images contributes to the fact that the value of health becomes objectively important; it acquires a particular personal sense and is projected into everyday life as behavior focused on health maintaining. The value of health represents psychological means for personal self-development.